Fatores preditivos de sintomas do transtorno do espectro autista em bebês prematuros: atenção compartilhada, linguagem e comportamentos atípicos - Vieira, Elisangela dos Anjos Paula (2018)
The Autism Spectrum Disorder (ASD) occurs in an estimated proportion of 1% of the child population, significantly affecting the individuals, their families and the society, with consequent problems to social interactions. ASD is characterized by significant and persistent deficits in social interaction and communication and by restrictive and repetitive patterns of behaviors, interests and activities. Recent guidelines suggest that ASD should be screened from 18 months, but it is not uncommon for children with this disorder to reach older ages without a diagnosis, hindering interdisciplinary intervention strategies. Furthermore, preterm birth (before 37 full weeks of gestation) is an important risk factor for developmental problems - including ASD. Thus, it is essential to recognize and assess potential early predictive factors for the development ASD symptoms in low-risk and high-risk samples. We hypothesize that difference in social-communication (expressive and receptive language), social-interaction (joint attention) and behavioral (atypical behavior) abilities at 12 months corrected age will be longitudinal predictors (at 18 months corrected age) of symptoms in the autistic spectrum. For this aim, we assessed 26 preterm and 21 term infants. The study is longitudinal in nature and divided into Moment A and Moment B, during which the two pillars that make up the ASD diagnosis –communication and social interaction problems and presence of atypical behaviors – were be assessed. In Moment A (12 months), infants were assessed using The Early Social Communication Scales, to evaluate joint attention; The Bayley Scales of Infant and Toddler Development–III, which offer information on the development of expressive and receptive language abilities; the Repetitive Behavior Questionnaire-2, RBQ-2 and a socio-demographic questionnaire. In Moment B (18 months) we added the Modified Checklist for Autism in Toddlers – MCHAT. The procedures were carried out in the Cognitive and Social Neuroscience Laboratory. Overall, results point to early signs of receptive and expressive language alterations at 12 months, as predictive factors of the level of symptoms compatible with an ASD at 18 months. Between group comparisons showed differences in language skills, response to joint attention, as well as in the level of autistic symptoms, with the preterm group being more impaired than the term group. Associations between greater prematurity (associated with low birth weight) and lower level of psychomotor development, less xi initiation of joint attention and more unusual sensorial interests were also verified. Our study contributes with important information about the possible early changes in this high-risk group, contributing to the understanding of early atypical trajectories in children who develop ASD.